High prevalence of alcohol- and substance abuse among young heart failure patients in Sweden. (25th November 2020) - Lindgren, M; Habtemichael, L; Rosengren, A; Schaufelberger, M
Abstract: Background: Heart failure in the young is increasing. Increasing prevalence of overweight and obesity may be of importance. While alcohol and drugs are known to have cardiotoxic effects, few studies have investigated the prevalence of alcohol- or substance abuse among young patients with HF. Aim: To investigate the prevalence of alcohol- and substance abuse in a cohort of young patients with heart failure. Methods: All patients that received a diagnosis of heart failure at Sahlgrenska University Hosital (Sweden) between 1997 and 2016, ages 18–54, with a previously documented transthoracic echocardiogram were included. A systematic evaluation of participants electronic health records was performed, where predefined details about the use of alcohol, narcotic drugs and anabolic steroids, as well as echocardiographic findings were recorded. Result: A total of 1363 patients were included (1001 men and 366 women, mean age 45 years), 190 (14%) of which were <34 years, 304 (22%) 35–44, and 869 (64%) 45–54 years. In total, a record of either alcohol- or substance abuse was found in 28% of men and 9% of women, respectively. The prevalence of Anabolic steroids was found to be 2% among men. For substance abuse, the prevalence was found to be 12% in men and 5% in women. Alcohol abuse was found in 24% of men and 5% of women. Both alcohol- and drug abuse was most common in the highest age group. Conclusion: There was a high prevalence of alcohol- and/or drug-abuse among young adults with heart failure, especially in male patients. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Swedish state under the agreement concerning research and education of doctors [grant number ALFGBG-427301]; The Swedish Society for Physicians, the Health & Medical Care Committee of the Regional Executive Board, Region Västra Götaland, Sweden, and the Swedish Heart and Lung Foundation [grant number 2015-0438]